3D printing of titanium parts from titanium hydride powder by solvent jetting on granule beds. (November 2020) - Carreño-Morelli, E.; Rodriguez-Arbaizar, M.; Cardoso, K.; Nagaram, A.B.; Girard, H.; Rey-Mermet, S.
Abstract: Titanium parts are produced by the "Solvent on granules 3D-Printing" technique (SG-3DP). Angular Titanium Hydride powders are used. A special purpose table-top machine, designed and built in a previous development, is used to print green parts, which are subsequently debinded, dehydrided and sintered in a muffle furnace. Porous electrode plates are produced with and without hole grids. The parts exhibit good shape preservation, with open interconnected porosities between 55 and 59%. The microstructure is characterized by optical metallography and scanning electron microscopy. In addition, experimental watch cases have been successfully printed and sintered. The results show the feasibility of using hydride powder for 3D-Printing of complex parts with good shape preservation. Highlights: "Solvent on granules 3D-Printing" is an effective Additive Manufacturing route to produce titanium parts from titanium hydride powder Granules prepared from angularTiH2 powder 3D-printed porous parts (open porosity of interest for electrolyser plates) Complex watch case shows good shape retention after debinding, dehydriding and sintering